Inorganic carbon, pH and alkalinity in the Canary Current Large Marine Ecosystem - González-Dávila, Melchor; Santana-Casiano, J. Magdalena (IOC-UNESCO, 2015)
The vertical distribution of the carbon dioxide (CO2) variables in the Canary Current Large Marine Ecosystem (CCLME) along the last fifteen years have clearly indicated significant changes over, at least, the first 1000 m affecting the inorganic carbon content and the acidity of the seawater. In the surface, the normalized total dissolved inorganic carbon increased at a rate of 0.9 mol kg-1, the pH in total scale decreased each year on average 0.0019 units, while the normalized total alkalinity keeps constant at a value of 2292 mol kg-1. This increase in total dissolved inorganic carbon (CT) is controlling the total column inventory of anthropogenic CO2 that has reached a value of 66 ± 3 mol m-2 for the reference year 2000. It has been shown that upwelled waters in the Mauritanian upwelling area provide high contents of inorganic carbon that lead to low calcium carbonate saturation states. The uptake of carbon by phytoplankton acts by decreasing CT and consequently increasing saturation states. The Eastern North Atlantic Ocean at the CCLME is increasing its storage capacity for excess CO2 by 0.85 mol m-2 yr-1. Model results indicate the importance of physical and environmental conditions in shaping the sensitivity of CCLME to potential climate change induced upwelling-favorable wind intensification. Published